Perceraian Akibat Kekerasan Rumah Tangga Studi Komparatif Indonesia dan Turki - Yeni Yenubah (State Islamic University of Kiai Haji Achmad Siddiq Jember, 2025)
The purpose of this research is to be able to answer the philosophical and conceptual basis for domestic violence that occurs between Indonesia This research is a juridical-normative literature research with two approaches in the form of a statutory approach and a conceptual approach. The data sources used are primary legal materials in the form of Law No. 1 of 1974 concerning Marriage, Compilation of Islamic Law and The Turkish Family Law of Cyprus 1951. To support primary legal materials, researchers also use secondary legal materials sourced from books, articles or other scientific research results. The result of this study is that the regulation of domestic violence between Turkey and Indonesia is located in the provision of punishment, where in Turkey in article 22 provides a fine for husbands who hurt their wives. Whereas in Indonesia it is regulated in Law Number 23 of 2004 concerning the Elimination of Domestic Violence (KDRT). The law regulates very strictly various forms of domestic violence, and legal sanctions for perpetrators are imprisonment and compensation / fines. Keywords: Divorce, Domestic Violence Abstrak: Tujuan penelitian ini adalah dapat menjawab landasan filosofis dan konseptual atas kekerasan dalam rumah tangga yang terjadi di Indonesia Penelitian ini merupakan penelitian Kepustakaan yang bersifat penelitian yuridis-normatif dengan dua pendekatan berupa pendekatan perundang-undangan dan pendekatan konseptual. Sumber data yang digunakan ialah bahan hukum primer berupa Undang-Undang No. 1 tahun 1974 tentang Perkawinan, Kompilasi Hukum Islam dan The Turkish Family Law of Cyprus 1951. Untuk mendukung bahan hukum primer, peneliti juga menggunakan bahan hukum sekunder yang bersumber dari buku, artikel atau hasil penelitian ilmiah lainnya. Hasil penelitian ini ialah bahwasanya pengaturan kekerasan dalam rumah tangga antara Turki dan Indonesia adalah terletak pada pemberian hukuman, dimana di turki pada pasal 22 memberikan denda bagi suami yang menyakiti istrinya. Sedangkan di Indonesia diatur dalam Undang-Undang Nomor 23 Tahun 2004 tentang Penghapusan Kekerasan Dalam Rumah Tangga (KDRT). Undang-undang tersebut mengatur dengan sangat tegas berbagai bentuk kekerasan dalam rumah tangga, dan sanksi hukum bagi pelakunya adalah hukuman penjara dan ganti rugi/denda.